Assessing the gap between GHG emissions and productivity in brazilian agriculture - Bragaganolo, Cassiano; Tateishi, Henrique Ryosuke (Universidade Federal de São Carlos, 2024)
Brazil's agricultural sector has seen significant economic growth due to increased productivity, yet its greenhouse gas (GHG) emissions have risen by about 2.5% annually. This study examines Total Factor Productivity (TFP) and GHG emissions in Brazilian municipalities from 2006 to 2017. It compares standard TFP measures with those considering GHG emissions, finding lower growth and efficiency in the latter. TFP growth didn't lead to emissions reduction; 65% of municipalities didn't control emissions while improving productivity. The study also highlights the need to monitor environmental efficiency in Brazilian agriculture, a topic overlooked in existing literature.
Avaliando a lacuna entre as emissões de GEE e a produtividade na agricultura brasileira
Keywords: GHG emissions; Total factor productivity; Green productivity; 2. Fome Zero e Agricultura Sustentável